Inhibition of IKK/NF-κB Signaling Enhances Differentiation of Mesenchymal Stromal Cells from Human Embryonic Stem Cells - Peng Deng; Chenchen Zhou; Ruth Alvarez; Christine Hong; Cun-Yu Wang (Stem Cell Reports, 2016)
Embryonic stem cell-derived mesenchymal stromal cells (MSCs; also known as mesenchymal stem cells) represent a promising source for bone regenerative medicine. Despite remarkable advances in stem cell biology, the molecular mechanism regulating differentiation of human embryonic stem cells (hESCs) into MSCs remains poorly understood. Here, we report that inhibition of IκB kinase (IKK)/nuclear factor kappa B (NF-κB) signaling enhances differentiation of hESCs into MSCs by expediting the loss of pluripotent markers and increasing the expression of MSC surface markers. In addition, a significantly higher quantity of MSCs was produced from hESCs with IKK/NF-κB suppression. These isolated MSCs displayed evident multipotency with capacity to terminally differentiate into osteoblasts, chondrocytes, and adipocytes in vitro and to form bone in vivo. Collectively, our data provide important insights into the role of NF-κB in mesenchymal lineage specification during hESC differentiation, suggesting that IKK inhibitors could be utilized as an adjuvant in generating MSCs for cell-mediated therapies.